The Importance of Nutritional Food Education for Pregnant Women - Qori Jabal Rahmah; Rahma Savira Salsabila; Rizky Astuti (Presscience, 2022)
The nutritional needs of pregnant women in each trimester are different, this is adjusted to the growth and development of the fetus and the health of the mother. The purpose of this research was to determine the importance of nutrition for pregnant women. The method used in this research is literature review. Selection of journal articles according to inclusion criteria and exclusion criteria. The inclusion criteria in this study included journals on nutrition for pregnant women, pregnant women with anemia, pregnant women with chronic lack of energy, journal articles in the last 5 years. Exclusion criteria included pregnant women who consumed nutritious food. The results of this study found that nutrition in pregnant women can cause disturbances to pregnant women and also the fetus they contain. Nutrition in pregnant women is influenced by knowledge, the higher the knowledge of pregnant women, the lower the risk of pregnant women being affected by disorders during pregnancy, pregnant women should eat a lot of foods that contain protein, vegetables and fruits that contain lots of vitamins. If nutrition is inadequate, it will cause various complications of pregnancy, including anemia, chronic lack of energy, premature birth, low birth weight (LBW), bleeding during delivery and infection.